Projeto, implementação e testes de um amplificador de áudio de alta fidelidade para fones de ouvido - Sanchez, Cassiano (Universidade Federal de São Carlos, 2023)
In this monograph, a high fidelity audio amplifier with tone control for headphones was developed. Circuits are built on printed circuit boards using discrete components. Topologies were initially determined to be simulated and tested. A prototype was assembled in an aluminum metallic box with on and off buttons and connectors. The results obtained were satisfactory, the amplifier presented distortions below 0.5%, upper cutoff frequency above 20kHz and slew rate above the minimum required. The project met all the requirements initially determined.
Design, implementation and testing of a hifi audio amplifier for headphones
Keywords: Amplificador de áudio; Amplificador de fones de ouvido; Audio amplifiers; Headphone amplifiers; ENGENHARIAS::ENGENHARIA ELETRICA::CIRCUITOS ELETRICOS, MAGNETICOS E ELETRONICOS